Inovasi Pendampingan Bimbingan Belajar Anak Sekolah Dasar untuk Meningkatkan Motivasi Belajar - Suwandi; Widya Jati Lestari; Ilwan Syafrinal (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
This community service activity in the form of tutoring during the COVID-19 pandemic is the concern and responsibility of lecturers and students (HIMAKA) of Cirebon City Catur Insan Cendekia University in the field of education. The purpose of this community service activity is to motivate activity participants and overcome the saturation level of elementary school students in the Kalijaga Village, Cirebon City, who for more than 1 year have been doing the online learning process at their respective homes. This activity was attended by elementary school students who are in the neighborhood around Baperkam RW.12 Kalijaga Village, Cirebon City. The method of implementing this service activity is a survey of activity needs, activity plans, implementation of tutoring activities and evaluation of activities. The results of this community service activity in the field of education show the enthusiasm, motivation and enthusiasm of elementary school students in participating in this tutoring activity. The consistency of the academic community in carrying out community service activities in the field of education needs to be maintained and even improved in order to support the tri dharma of higher education.